(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Arthritis, also known as joint inflammation, is the swelling and tenderness of one or more joints in the body. With the main symptoms being stiffness of joints and pain, arthritis can severely affect the quality of life. It worsens with age and typically shows itself in adult ages. This case study is of a very young, 19-year-old woman, who was diagnosed with rheumatoid arthritis at the age of 18. After Ayurvedic assessment, she was recommended the use of herbal blends, oils, Ayurvedic diet, and lifestyle changes. This was done in gradual phases and lasted for about six months. The American College of Rheumatology’s Arthritis Impact Measurement Scales were used for pre and post assessment. Post Ayurvedic management, the client’s situation is greatly improved after Ayurvedic management and she still follows ayurvedic recommendations for maintenance. This case study provides positive insights and alternatives into the management of Arthritis.